Construct Validity of Almutairi's Critical Cultural Competence Scale. (June 2017) - Almutairi, Adel F.; Dahinten, V. Susan
Cultural diversity in health care settings can threaten the well-being of patients, their families, and health care providers. This psychometric study evaluated the construct validity of the recently developed four-factor, 43-item Critical Cultural Competence Scale (CCCS) which was designed to overcome the conceptual limitations of previously developed scales. The study was conducted in Canada with a random sample of 170 registered nurses. Comparisons with the Cultural Competence Assessment instrument, Scale of Ethnocultural Empathy, and Cultural Intelligence Scale provided mixed evidence of convergent validity. Modest correlations were found between the total scale scores suggesting that the CCCS is measuring a more comprehensive and conceptually distinct construct. Stronger correlations were found between the more conceptually similar subscales. Evidence for discriminant validity was also mixed. Results support use of the CCCS to measure health care providers' perceptions of their critical cultural competence though ongoing evaluation is warranted.